2017
DOI: 10.1016/j.mad.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and risks of meta-analyses of longevity studies

Abstract: Searching for genetic determinants of human longevity has been challenged by the rarity of data sets with large numbers of individuals who have reached extreme old age, inconsistent definitions of the phenotype, and the difficulty of defining appropriate controls. Meta-analysis – a statistical method to summarize results from different studies – has become a common tool in genetic epidemiology to accrue large sample sizes for powerful genetic association studies. In conducting a meta-analysis of studies of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…iii) The most recent paper -and also the largest in term of sample size -was published in 2016 by Erickson and colleagues 115 , but the authors studied an "healthy ageing" phenotype, based on self-reported data (called by the author Wellderly, in subjects aged 84.2 ±9.3 years). The age range of the study indicates that very limited information regarding longevity have been investigated 116 .The main result of this study is the association with healthy aging in loci in the COL25A1 gene encoding for a protein secreted in the brain and associated to amyloid plaques.…”
Section: And Bymentioning
confidence: 91%
See 1 more Smart Citation
“…iii) The most recent paper -and also the largest in term of sample size -was published in 2016 by Erickson and colleagues 115 , but the authors studied an "healthy ageing" phenotype, based on self-reported data (called by the author Wellderly, in subjects aged 84.2 ±9.3 years). The age range of the study indicates that very limited information regarding longevity have been investigated 116 .The main result of this study is the association with healthy aging in loci in the COL25A1 gene encoding for a protein secreted in the brain and associated to amyloid plaques.…”
Section: And Bymentioning
confidence: 91%
“…Thus, a recent paper -in order to avoid problems of inconsistency in the definition -suggests that longevity has to be defined according to percentile survival based upon the reference birth cohort for each population, indicating that the environmental context play a critical role on this specific phenotype. One percentile survival is the threshold suggested to maximize the probability to identify genetic association 7 . Moreover familial longevity is also a criteria used in the study of the genetics of human longevity: the GEHA (Genetics of Healthy Ageing) Study includes nonagenarian sibling pairs to select families enriched for genetic influences on longevity 8 .…”
Section: The Complexity Of Human Longevity 21 the Definition Of Lonmentioning
confidence: 99%
“…The e 3 allele is the “neutral allele” in many ethnicities, while e 2 is the least common allele that emerged as a longevity variant when Schachter et al noted an increased frequency of e 2 in French centenarians (Schachter et al, ). Since then, several studies have provided evidence that e 2 has a beneficial neuroprotective effect (Kim et al, ), decreases neuroinflammation (Dorey, Chang, Liu, Yang, & Zhang, ), and promotes longevity (Sebastiani, Bae, et al, ; Sebastiani, Gurinovich, et al, ; Sebastiani et al, ) and healthy aging (Kulminski et al, ; Wu & Zhao, ). Therefore, we hypothesize that targets of this allele may lead to the discovery of treatments that help maintain good cognitive function and escape cognitive impairment with aging.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of high-throughput technologies is enabling the acquisition of large data sets on genetics, genomics and many cell variables, including proteins, lipids and metabolites in an effort to (1) untangle the intricate biological process of aging, (2) identify drug targets, and (3) develop therapeutics to enhance life and health span. Individually these datasets have contributed to our understanding of human physiology and diseases but existing approaches fall short in terms of understanding the complex role of those mechanisms in aging that protect individuals from age-related diseases and enable health and life span (Sebastiani et al, 2013(Sebastiani et al, , 2017aMilman and Barzilai, 2015). The application of GWAS, Mendelian randomization and other similar approaches have been of limited success and have not resulted in any major breakthroughs in therapeutics for prevention of age-related diseases, including Alzheimer's Disease (AD).…”
Section: Introductionmentioning
confidence: 99%